Smart CSR Strategies for Sustainable Development: Evaluating Public-Private Collaboration in Gresik Regency - Barham Siregar; Agus Sukristyanto; Rachmawati Novaria (Department of Public Administration, 2026)
Corporate Social Responsibility (CSR) is an important instrument for social, economic, and environmental development, particularly in industrial regions such as Gresik Regency. However, regional CSR practices still face governance problems, including philanthropic tendencies, short-term programs, fragmented implementation, weak reporting systems, and limited impact measurement. This study develops Smart Corporate Social Responsibility (Smart CSR) as a governance model and evaluative framework to strengthen collaboration among local government, companies, and communities. Using a qualitative case study design, data were collected from regional regulations, CSR reports, official government publications, observations, and semi-structured interviews with government actors, companies, beneficiary communities, and supporting stakeholders. Data were analyzed through inductive-deductive thematic analysis and an audit trail linking empirical evidence, themes, theory, and model development. The findings reveal a gap between the regulatory framework and implementation. Although local regulations provide a legal basis, company reporting remains limited, programs are dominated by short-term activities, coordination and community participation are inconsistent, and impact indicators are not standardized. Smart CSR integrates data-driven needs mapping, multi-actor role distribution, digital reporting, community participation, ESG/SDGs-based evaluation, and shared value creation. The model contributes to CSR, collaborative governance, and sustainable development literature in industrial regions of developing countries.